CERPEN TUSING ULIAN I SEPI, BLI KADEK, DAN CUCU DALAM PUPULAN CERPEN BLI KADEK : ANALISIS PSIKOLOGI SASTRA - Sukmayanti, Ni Nyoman Eni (Humanis, 2014)
This research entitle "Cerpen Tusing Ulian I Sepi, Bli Kadek, Dan Cucu Dalam Pupulan Cerpen Bli Kadek : Analysis Psychology". this short story masterpiece Putu Nopi Suardani is analysed by using art psychology theory. Third of this short story draw to be checked because expressing psychological at story figure when residing in at atmosphere like, sorrowfully, and strained. As for target of this research is to obtain; get clear picture regarding hit existing psychological aspect in third the short story. Theory used to analyse art psychology aspect is pikoanalisis theory from Sigmund Freud. Method used to collect data is book study method with technique note and translation, later; then to analyse data used by method qualitative with analytic descriptive technique. Caught up with presentation analyse data, data which have been collected, to be analysed, and is finally presented in skripsi format by using informal method and technique think inductive deductive. Result of this research in the form of psychological aspect from each short story cover id, ego, and superego, which can seen to through its story structure.
Keywords: short story, structure , psychology